Analysis of prognostic factors of endoscopic optic nerve decompression in traumatic blindness. (November 2013) - Song, Yexun; Li, Heqing; Ma, Yanhong; Li, Wei; Zhang, Xiaowei; Pan, Xueying; Tan, Guolin
Abstract Conclusions: Hemorrhage within the ethmoid and/or sphenoid sinus and an interval between the time of injury and the time of operation exceeding 3 days are the risk factors for the visual prognosis of traumatic blindness. Objectives: To investigate the therapeutic efficacy of endoscopic optic nerve decompression in the treatment of traumatic blindness and to evaluate the relevant prognostic factors. Methods: Eighty-five cases of traumatic blindness were analyzed retrospectively. Univariate analysis and multiple logistic regression were performed to evaluate potential prognostic factors. Results: The overall rate of vision acuity improvement was 44.7% (38 of 85). Univariate analysis indicated that hemorrhage within the ethmoid and/or sphenoid sinus was significantly associated with unrecovered visual acuity. However, multiple logistic regression analysis identified that an interval between the time of injury and the time of operation exceeding 3 days, and hemorrhage within the ethmoid and/or sphenoid sinus were significantly correlated with the efficacy of treatment of traumatic blindness.